(untitled) (Research, Society and Development, 2021)
The present study aimed to identify in the literature the nurse’s assistance for COVID-19 in primary care. It is an integrative literature review, of a descriptive nature, with a qualitative approach. Data collected between the months of January to March 2021, using a protocol based on the PICO strategy, using controlled descriptors and keywords, crossed with Boolean operators OR and AND, on the Virtual Health Library (BVS), Latin Literature platforms American and Caribbean Health Sciences (LILACS), The Scientific Electronic Library Online (SciELO), Nursing Database (BDENF), PUBMED and Google Scholar in the period from 2009 to 2021. The final products were 15 articles and four included other studies, through other free searches and gray literature, that met the inclusion criteria. With this study it was observed that the assistance of the professional nurse in the APS units for COVID-19 goes beyond the assistance to the individual, because, when carrying out his actions and developing them, he ends up carrying out the prevention for the virus in the individual, family or community. In this way, their assistance is developed in carrying out clinical / educational actions and implementing the SAE, thus avoiding the increase in the number of cases of COVID-19 in the community.